Lynch syndrome associated endometrial carcinomas in Western Australia: an analysis of universal screening by mismatch repair protein immunohistochemistry. Issue 6 (15th April 2021) - Gupta, Surabhi; Nichols, Cassandra B; Phillips, Jessica; O'Sullivan, Sarah; Ayres, Chloe; Mohan, Ganendra Raj; Leung, Yee; Stewart, Colin J.R.; Tan, Adeline; Schofield, Lyn; Salfinger, Stuart G; Kiraly-Borri, Catherine; et al.
Abstract : Background: In 2016 universal screening with mismatch repair protein immunohistochemistry in all newly diagnosed endometrial carcinomas was introduced in Western Australia. Objective: To compare the prevalence of Lynch syndrome associated endometrial carcinomas between 2016 and 2019 with a historical control (2015). Additionally, to compare the number of cases appropriately referred for genetic assessment. Methods: A cross-sectional study of cases presented at the Western Australia gynecologic oncology tumor board was carried out. The primary outcome was the prevalence of Lynch syndrome associated endometrial carcinomas. A secondary outcome was the number of cases appropriately referred for genetic assessment. The following variables were extracted: date of birth; age at diagnosis; vital status; tumor mismatch repair protein expression status (retained or lost) and if lost, the specific mismatch repair protein deficiency; patients who were referred to a genetic clinic; and family history, if recorded. Data were collected from the clinical databases of the Familial Cancer Program at Genetic Services of Western Australia and WOMEN Center, to determine whether patients were appropriately referred for genetic evaluation and to ascertain the results of genetic testing. Results: Between 2016 and 2019, there were 1040 new endometrial carcinomas. Tumors of 883 (85%) patients underwent mismatch repair protein immunohistochemistry compared with 117 of 199 patients (59%) in 2015 (χ 2 73.14, p<0.001). Of 883 tumors tested, 242 (27%) showed loss of mismatch repair protein expression. In 2015, 30 (26%) tumors of 117 tested showed loss of mismatch repair protein expression. During the 4 years of universal screening, 13 (1.5%) of 883 patients screened were diagnosed with Lynch syndrome compared with 2 (1.7%) of 117 in 2015 (Fisher's exact test 0.04, p=0.69). In 2015, 11 (37%) of 30 patients with loss of mismatch repair protein expression were not referred for genetic assessment compared with 36 (17%) of 209 patients in the universal screening group (χ 2 6.28, p=0.02). No cases of Lynch syndrome were diagnosed in patients aged over 70 years. Conclusions: Universal immunohistochemical screening did not increase the proportion of Lynch syndrome associated endometrial carcinomas identified, although the study was underpowered to detect small differences. There was an improvement in appropriate referrals for genetic assessment.